Síntese estereosseletiva de α-fenilseleno-β-amino ésteres pela reação do tipo-Mannich e efeito promotor de tiofenol na reação de Pictet-Spengler. - Vieira, Adriano Siqueira (2006)
In the present work, it was developed a new methodology for the stereoselective synthesis of α-phenylseleno-β-amino esters by the Mannich-type reaction. These reactions involve chlorotitanium α-phenylseleno esters enolates and aromatic aldimines, affording preferentially the syn-α-phenylseleno-β-amino esters 3a-l in reasonable to good diastereoselectivity, and in 67% to 86% yield. The reactions were carried out with aromatic aldimines with differents substitution paterns in the aromatic ring. Testing the reactivity and the synthetic potential of the α-phenylseleno-β-amino esters, it was observed that the compound 3a reacts with LiHMDS in mild reaction conditions to aford the corresponding anti-α-phenylseleno-β-lactam 4 in 57% yield. Additionally, it was developed an efficient methodology for the synthesis of 1,2,3,4-tetrahydroisoquinolines 7 substituted in the carbon 1, by the activated Pictet-Spengler reaction in the presence of thiophenol, which produces a considerable promoting effect. This reaction was performed with N-tosyl-β-phenethylamines 5 and phenylthioacetals, which were produced 'in situ' by the reaction of thiophenol with an aldehyde under BF3.Et2O catalysis, affording the 1,2,3,4-tetrahydroisoquinolines 7 in 66 to 94% yield.